The year of what if - Patrick, Phaedra (Park Row Books, 2024)
Visiting a fortune teller before her wedding, Carla Carter, when it is revealed that a different man holds the key to her happiness, someone she met 21 years ago, she embarks on a journey to find her perfect match, hoping a face from her past will help break her family's curse.